EVALUATION OF HUMAN ACTIVITIES ON GROUNDWATER QUALITY ON SOME SELECTED MARKETS IN ABEOKUTA NORTH AND SOUTH LOCAL GOVERNMENT SOUTHWEST NIGERIA - Adekitan, Adetoun (FUDMA Journal of Sciences, 2026)
Anthropogenic activities and inadequate waste management significantly pollutes groundwater quality. This study evaluates the extent of this contamination in groundwater sited proxy to selected markets of Abeokuta North and South Local Government Areas Southwest Nigeria. Twelve (12) Groundwater samples were purposively selected from 4(four) location namely: Itamorin, Lafenwa, Adatan, and Kuto market and analysed for physico-chemical (pH, temperature, electrical conductivity, Biological Oxygen Demand, chloride, sulphate and total hardness) as well as microbiological (TBC, TCC, TEC) parameters. Result showed that the Biological Oxygen Demand (BOD) values were higher than the (WHO, 2022) guideline which was observed in Adatan Sample One (1). Phosphate concentrations were higher in most the samples, exceeding the 5 mg/L WHO guideline, given as 47.34 mg/L in Kuto Sample 2. The widespread of bacteriological contamination was observed in Total Coliform Counts for all the samples, and Total E. coli Counts were also found in all samples. Lafenwa has the highest value of (4.8x10² cfu/ml) for TEC, given as 0cfu/ml. These results strongly indicate faecal contamination and organic pollution, directly linked to inadequate sanitation, poor waste disposal practices, and market activities. Human activities in the selected markets of Abeokuta are significantly degrading groundwater quality, posing substantial health risks. Urgent interventions are required, including improved waste management, enhanced sanitation infrastructure, and regular monitoring, to protect public health and ensure sustainable groundwater use.